Assessment of sábalo (Prochilodus lineatus) fisheries in the lower Paraná River basin (Argentina) based on hydrological, biological, and fishery indicators - Baigún, Claudio Rafael M. (2013)
This study assesses the change in fish exploitation patterns of the sábalo fisheries of the lower Paraná River basin based on hydrological, biological, and fishery indicators. From historical catch records, we recorded a shift from a lightly and moderate exploited status before 2001 to a heavily exploited one, as a result of the development of sábalo exports from 2001 onwards. Channel and floodplain connectivity indices demonstrated that the Paraná exhibited highly favorable hydrological conditions between 1972 and 1999 but more adverse conditions from 1999 to 2009, as a consequence of flood pulses reduction coincident with a fishing mortality increment. A total catch of 15,000 tons, including local consumption, regional market, informal sales, and exportation volumes, was estimated as the maximum sustainable catch. That level was instead exceeded 3 fold in 2004, in parallel with a decrease in the mean fish length from 48 to 42 cm, along with a reduction in both the mesh size from 16 to 12 cm and megaspawner proportion, and an increase of fishing mortality. Although growth overfishing was not noted, an analysis of the spawning potential ratio trend indicated that recruitment overfishing took place during 2005, since the fishing mortality rate was 4 times greater than the natural mortality rate. These observations suggest that less favorable hydrological conditions after 1999 coupled with a coincident high fishing pressure could have impacted the sábalo population biomass. Managementof sábalo fisheries requires to set aside a single economic vision of the resource use moving to an ecosystem-oriented approach that incorporate, among others components, the hydrological regime, species life history traits, fishing impacts on other species, and main stakeholders socioeconomic requirements as key elements for the preservation of fishery sustainability